Determination of the stability constants of the proton and Cu(II) complexes of 2-(4-dimethylaminocinnamalamino)phenol in binary solvent mixtures by the potentiometric method - Cankurtaran, H; Kunt, G; Yalçin, M (EDITURA ACAD ROMANE, 2004)
The successive formation constants of copper(II) and proton complexes of the Schiff base, 2-(4- dimethylaminocinnamalamino)phenol (DACAP) formed by condensation reaction of 4-dimethylaminocinnamaldehyde and 2-aminophenol were determined in the aqueous solutions of acetone and dioxane at 25 +/- 0.1degreesC and an ionic strength of 0.1 M by potentiometric pH measurements. Calculations were performed with the weighted least square method by means of the PKAS and BEST computer programs. The distribution diagram of the complex species was drawn as a function of the pH. The solvent effect on different protonation sites of the Iigand was discussed. Some characteristic specifications of the ligand and the copper(II) complex were also described. Together with the formation of [CuL](+) and CuL2 complexes, the presence of CuL(OH)(n)((n-1)-), hydroxo complexes were also observed at rather basic region and their corresponding formation constants were determined.
Keywords: CINNAMALDEHYDE; WATER; ACID; Chemistry